Enhancement of Gielis' Supershapes in generating nature motifs / Rafizah Kechil ... [et al.] - Kechil, Rafizah; Abdul Razak, Noor 'Aina; Mohamed, Siti Asmah; Ahmad Shukri, Fuziatul Norsyiha (Universiti Teknologi MARA, Perak, 2021)
Nature motifs have played an important role in designing and generating most products such as jewellery, fashion, furniture, textile, or visual arts. The designers may translate their ideas by using the mathematical equations to design the products inspired by the nature motifs. One of the mathematical equations that can be used in creating or designing nature motifs is the Gielis' Supershape (GS). This formula has been introduced by Johan Gielis, who is a botanist and mathematician. In this paper, we discuss the nature motif that can be created using the GS. We also proposed the Enhanced Gielis' Supershape (EGS) and present some comparisons. The result shows that the nature shape created by using the EGS was more impressive compared to the shape created using the original GS.